Zoon Balanitis and Lichen Sclerosus: An Uncommon Association - Pedro Miguel Garrido; Marta Aguado-Lobo; Luís Soares de Almeida; João Borges da Costa (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Zoon balanitis and lichen sclerosus are both chronic inflammatory disorders of the genital mucosa that usually affect middle-aged or elderly uncircumcised men. Although the precise etiology of Zoon balanitis is still unclear, a pathogenic role of irritant and mechanical factors has been suggested. Therefore, foreskin sclerosis and phimosis caused by male genital lichen sclerosus may trigger the development of Zoon balanitis. However, until the present, only three cases with clinical and histopathologic features consistent with synchronous presentation of both disorders have been described. We report the case of a 70-year-old male who developed Zoon balanitis in association with lichen sclerosus, that cleared only after circumcision.